Pengaruh Pelatihan Terhadap Produktivitas Kerja Pegawai Pada Gardu Induk Haurgeulis PT. PLN (Persero) Kecamatan Haurgeulis Kabupaten Indramayu - Lucky Sukma; Suroso Suroso; Flora Patricia Anggela (Peneliti.net, 2022)
This study aims to analyze: (1) Data regarding the training of employees of the Haurgeulis Substation PT. PLN (Persero). (2) Data on work productivity of employees of the Haurgeulis Substation PT. PLN (Persero). (3) Data on the effect of training on work productivity for employees of the Haurgeulis Substation PT. PLN (Persero). The subjects of this study were employees who worked at the Haurgeulis Substation PT. PLN (Persero) Haurgeulis District, Majalengka Regency, amounting to 18 people. Data were collected by observation and questionnaires. The analysis used is descriptive percentage analysis, simple regression analysis and hypothesis testing. The results of this study indicate that: (1) The training for employees of the Haurgeulis Substation PT. PLN (Persero) has reached more than 60% which is proven, this can be seen from the t count value of more than t table (4.103 > 2.120). (2) The work productivity of the employees of the Haurgeulis Substation PT. PLN (Persero) has reached more than 60%, which is proven, this can be seen from the t arithmetic value of more than t table (4,091 > 2,120). (3) Training has a positive and significant effect on the work productivity of the employees of the Haurgeulis Substation PT. PLN (Persero). This is evident from the value of tcount > ttable (3.764 > 2.120).